Hubungan Tingkat Pengetahuan Ibu Dengan Upaya Pencegahan Rampan Karies Pada Anak Pra Sekolah Di Bimba Aiueo Subang - Hartini, Yayu; Laela, Dewi Sodja; Octaviana, Devy; Fatikhah, Nurul (Jurnal Terapi Gigi dan Mulut, 2024)
Dental caries is one of the most common diseases in Indonesian society, both in adults and children. The common form of caries that mostly affects children under the age of five is referred to as rampant caries. Maternal ignorance about proper dental care in children is one of the factors in the onset of rampant caries in children. Maternal knowledge and efforts towards children's dental and oral hygiene have a significant influence on children's attitudes and behaviors that will complete children's dental health in the future. This study aims to determine the relationship between the level of maternal knowledge and efforts to prevent caries rampant in pre-school children at Bimba AIUEO Subang. Analytic research with cross-sectional design method. In Bimba AIUEO Subang, 60 people, including 30 mothers and 30 children, participated in the sampling process. The results showed that mothers' knowledge about caries rampant was found to be in the good category, caries rampant cases most children did not experience caries rampant and mothers' efforts in preventing caries rampant were found to be in the good category. The research hypothesis was tested using the Fisher Exact test showing a p value = 0.007 (p <0.05). The relationship between maternal knowledge is proven to have an effect on efforts to prevent caries rampant in pre-school children. Increasing maternal knowledge and efforts to care for children's teeth plays an important role in preventing caries rampant by familiarizing children to always maintain dental health and dental hygiene.